(untitled) (Medical Forum Monthly, 2020)
Objective: To explore the development of depression in patients undergoing rhinoplasty. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Halcyon Medical Centre Lahore, July 2018 to March 2020. Materials and Methods: It is a cross-sectional study consisting of 38 patients. Out of these 10 patients were male and 28 females. 35% patients went through this surgery for medical reasons while remaining for aesthetic purposes. Follow up plan for rhinoplasty patients already in place at our Halcyon Medical Centre Lahore. All the patients coming for follow up after rhinoplasty were properly assessed for the complications one can have after rhinoplasty. Patients who showed signs and symptoms of major depression were assessed in detail for early identification and management. Results: Out of 38 patients undergoing rhinoplasty, only 5 patients showed signs of major depression. Four of these were females and one male. Total percentage of affected individuals was 13 % which might not be clinically significant but it seems to be more common among females as compare to men. Conclusion: Depression might not be a clinically significant post-operative complication of Rhinoplasty but still it can be troublesome for patients, their families and carers.